PENGEMBANGAN MODEL BAHAN AJAR BERORIENTASI MICRO DIDACTIC YANG MEMUAT PEMAHAMAN KONSEP PERTIDAKSAMAAN LINEAR DI SEKOLAH MENENGAH PERTAMA - Dayen Dayen; Mohamad Rif’at; Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe concept of inequality is a prerequisite for solving problems in other mathematical contextssuch as in linear programming, expressing the domain of functions, compiling trigonometricequations, and also optimizing geometric analytic. However, the teaching materials for thistopic is very few and there are also some misconceptions of students in solving linearinequalities. One of the alternatives for this problem is to develop a teaching material modelwith a didactic micro-orientation which contains an understanding of the concept of linearinequality based on NCTM (National Council of Teachers of Mathematics). This research isclassified as design and development research (DDR). Based on the validation results, thisteaching material model is very feasible to use with an average score of 3.28. Each indicatorregarding the suitability of concept descriptions in NCTM-based teaching materials withKompetensi Inti and Kompetensi Dasar, indicators of competency achievement, andmathematics learning objectives. Furthermore, the stages of NCTM-based teaching materialsare presented clearly so that they are easy to understand, the presentation flow is presentedcoherently, the questions are presented according to the concept, the presentation of thefindings at the beginning of the presentation of the concept of inequality is interesting.Keywords : Teaching Material Model, Understanding The Concept Of Linear Inequality,And Micro Didactic